2020
DOI: 10.1038/s41598-020-74309-0
|View full text |Cite
|
Sign up to set email alerts
|

MHC/class-II-positive cells inhibit corticosterone of adrenal gland cells in experimental arthritis: a role for IL-1β, IL-18, and the inflammasome

Abstract: In experimental arthritis, glucocorticoid secretion is inadequate relative to inflammation. We hypothesized that IL-1 is a key factor for inadequate glucocorticoid secretion in arthritic rats. Collagen type II—induced arthritis (CIA) in DA rats was the model to study effects of IL-1 on adrenal function. In the CIA model, an increase of intraadrenal MHCII-positive cells was observed. MHCII-positive cells or bone marrow-derived dendritic cells inhibited glucocorticoid secretion of adrenal gland cells. IL-1, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(57 reference statements)
0
5
0
1
Order By: Relevance
“…A more recent study showed that the adrenal cortex of a collagen‐induced arthritis rat model of severe human arthritis displayed a higher number of major histocompatibility complex class II (MHC‐II +) cells than the cortex of control rats, associated with suppression of ACTH‐induced secretion of GC by adrenocortical cells 33 (Table 2, Figure 2). In addition, treatment of adrenocortical cells with IL‐1b further reduced ACTH‐stimulated GC secretion, suggesting that local inflammation of the adrenal glands in arthritic rats may be a key mediator of reduced corticosterone production through MHC‐II + ‐expressing cells and IL‐1b secretion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study showed that the adrenal cortex of a collagen‐induced arthritis rat model of severe human arthritis displayed a higher number of major histocompatibility complex class II (MHC‐II +) cells than the cortex of control rats, associated with suppression of ACTH‐induced secretion of GC by adrenocortical cells 33 (Table 2, Figure 2). In addition, treatment of adrenocortical cells with IL‐1b further reduced ACTH‐stimulated GC secretion, suggesting that local inflammation of the adrenal glands in arthritic rats may be a key mediator of reduced corticosterone production through MHC‐II + ‐expressing cells and IL‐1b secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent advances in molecular biology and genetics have increased dramatically our understanding of the pathophysiological interactions between the inflammatory process, the immune system response and the HPA axis in the pathogenesis of RA, still many critical points remain unanswered. 33 Dark-Agouti rats: collagen type II-induced arthritis 1. The adrenal cortex of DA rats had higher number of MHC-II+cells compared with controls.…”
Section: Adrenocortical Dysfunction In Gctreatment Naïve Patients Wit...mentioning
confidence: 99%
“…For example, hypertension, T2D, and kidney diseases were proven to be associated with cerebrovascular damage [ 36 ]. Chronic inflammatory diseases could induce higher chemokine production and activate intrarenal macrophages and dendritic cells in rats [ 37 ]. This suggested that the kidneys may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are needed to firm up this conclusion since Aim2 was also expressed in BM. Other limitations of this study included (i) the lack of data comparing biomechanical properties of fractured bones from all the mutant mouse strains used; (ii) the unknown function of IL-18 pathway in fracture healing; (iii) the contribution of systemic factors such as glucocorticoids, which are regulated by inflammasome-IL-1β pathways and affect bone healing and strength ( Stangl et al, 2020 ; Blair et al, 2011 ; Hachemi et al, 2018 ); (iv) the knowledge gap on differential expression of GSDMD and GSDME by the various cell types that are activated in response to fracture; and (v) the lack of translational studies using drugs such as disulfiram, which inhibits the processing or functions of GSDMD and GSDME ( Wang et al, 2021 ), to validate genetic mouse findings. Despite these shortcomings, this study has revealed the crucial role that GSDMD and GSDME play in fracture healing ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%